Measurement of interaction between water droplets and curved super-hydrophobic substrates in the air - Zhiyi Wang; Meirong Zhao; Jile Jiang; Lele Zhang; Shuya Zhuang; Yuchen Zhao; Yinguo Huang; Yelong Zheng (AIP Advances, 2018)
The interaction force is very important in the study of the contact process of droplets and super-hydrophobic substrates. Accurate interaction force measurement in the air has far-reaching impact on industrial production and biomimetic field. However, limited by the evaporation of small droplets, interaction force can only be measured in the liquid by AFM and other devices. A millimetric cantilever was used to make it possible to measure the interaction between droplets and super-hydrophobic substrates in the air. The optical lever was calibrated with the electrostatic force. The super- hydrophobic substrates were fabricated using nano particles and copper grids. We finally acquired the interaction force and wetting time between the droplet and super- hydrophobic substrates with different grid fractions and similar contact angle. The results showed that the interaction force decreased with the increase of the grid fraction. These would open a new way of understanding the mechanism of hydrophobic.